PENGARUH PENDEKATAN SAINS TEKNOLOGI MASYARAKAT TERHADAP LITERASI SAINS SISWA PADA MATERI FLUIDA DINAMIS - Sari, Intan Wulan; Ayunda, Desy Sari; Sari, Nurmala; Mustari, Andi (Relativitas: Jurnal Riset Inovasi Pembelajaran Fisika, 2024)
This study aims to analyze the effect of Science Technology Society (STS) approach on students' scientific literacy in fluid dynamic material in physics subject. An experimental method with pretest-posttest control group design is used as a method in this study. The study population included all grade XI students of Senior High School Negeri 8 Banda Aceh who took sciences major, with a random sample that consisting 32 students in the experimental class and 32 students in the control class. An experimental class received learning treatment with STM approach, while the control class was not given a special treatment. Data were collected through an objective test of 25 questions, with the parameters measured was the scientific literacy ability of the science competency aspect and the science knowledge aspect. Data analysis was carried out using parametric analysis techniques, including normality tests, homogeneity tests, and t-tests for mean differences. The results showed that there was a significant difference between the pretest and n-Gain scores in the experimental and control class. An experimental class using the STS approach showed a higher increase in science literacy than control class, with a percentage of achievement was 86% in the science competency aspect and 88% in the science knowledge aspect. The STM approach has been proven effectively in improving students' scientific literacy skills in linking the concept of dynamic fluids with real applications in everyday life. The conclusion of this study is the STM approach has a positive influence on students' scientific literacy, more able to understand and apply science in social and technological contexts. This study contributes to develop more effective learning methods in schools science education.